A prospective study of the responsiveness of the original and the short form Berg Balance Scale in people with stroke. (May 2015) - Chen, Kuan-Lin; Chou, Yei-Tai; Yu, Wan-Hui; Chen, Cheng-Te; Shih, Ching-Lin; Hsieh, Ching-Lin
Objective: The study aim was to examine the responsiveness of the Berg Balance Scale (BBS) and that of its short form (SFBBS) at both the individual person level and the group level. Design: A repeated-measurements design. Setting: Hospital and home setting. Participants: Patients with stroke. Results: Totals of 226, 202, and 168 patients with stroke were assessed with the BBS at 14, 30, and 90 days after stroke, respectively. The SFBBS data were extracted from the patients' responses on the BBS. At the group level, the BBS and the SFBBS had sufficient and similar responsiveness. For the Rasch scores, the effect sizes of the three change scores for the BBS and the SFBBS, respectively, had similar ranges between 0.38 and 0.88 and between 0.39 and 0.85, respectively. The standardized response means of the three change scores for the BBS and the SFBBS ranged from 0.74 to 1.33 and from 0.72 to 1.13, respectively. At the individual person level, the BBS detected significant balance improvement in about twice as many patients as the SFBBS detected. Conclusion: The responsiveness of the BBS at the individual person level was better than that of the SFBBS in patients with stroke. The BBS is recommended as an outcome measure to better detect changes in individual patients.